2014
DOI: 10.17221/674/2014-pse
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi colonisation of Cry3 toxin-producing Bt maize and near isogenic maize

Abstract: Despite the fact that, on average, approximately 5-6 metric tons/ha of Bt maize stubble enter the soil on more than 170 million of hectares worldwide, the environmental impact of genetically modified maize plants on the arbuscular mycorrhizal fungi (AMF) is poorly known. In this study, the mycorrhizal colonisation on the roots of Bt maize (DAS-59122-7) and its near isogenic line was examined during the whole vegetation period. Cry3 toxin-producing Bt maize and its near isogenic line were grown in an experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The above mentioned studies were conducted in solo experimental conditions; Cheeke et al (2012b) performed a field experiment that compared nine types of transgenic Bt maize with their corresponding near-isogenic parental lines in greenhouse microcosms, which demonstrated that the Bt maize plants had lower levels of AMF colonization in their roots than did the non-Bt parental lines. Similar phenomena were observed by Nagar et al (2014), who found that DAS-59122-7 Bt maize had a negative effect on the initial development of AMF under field conditions. Other studies (Chen et al, 2016, 2017) hypothesized that the appressorium density, colonization intensity and arbuscule abundance were lower in Bt cotton roots (Jin26, GK12, and Jin 44, all of which expressedCry1Ac protein) than in roots in non-transgenic isolines (Jin7, Si3, and Ji492).…”
Section: Introductionsupporting
confidence: 86%
“…The above mentioned studies were conducted in solo experimental conditions; Cheeke et al (2012b) performed a field experiment that compared nine types of transgenic Bt maize with their corresponding near-isogenic parental lines in greenhouse microcosms, which demonstrated that the Bt maize plants had lower levels of AMF colonization in their roots than did the non-Bt parental lines. Similar phenomena were observed by Nagar et al (2014), who found that DAS-59122-7 Bt maize had a negative effect on the initial development of AMF under field conditions. Other studies (Chen et al, 2016, 2017) hypothesized that the appressorium density, colonization intensity and arbuscule abundance were lower in Bt cotton roots (Jin26, GK12, and Jin 44, all of which expressedCry1Ac protein) than in roots in non-transgenic isolines (Jin7, Si3, and Ji492).…”
Section: Introductionsupporting
confidence: 86%
“…The root colonization results of the current study support the findings of our previous field experiments but contradict those of a recent field study in which Bt maize‐expressing Cry34/Ab1 and Cry35Ab1 toxins had lower levels of AMF colonization in roots than its non‐ Bt isoline, 19 and 60 days after sowing (Seres et al . ). Differences in AMF root colonization between Bt and non‐ Bt maize have most often been reported 60 days or less after sowing, indicating that plant developmental stage may be an important contributor to differences in AMF colonization between Bt and non‐ Bt cultivars (Seres et al .…”
Section: Discussionmentioning
confidence: 97%
“…Differences in AMF root colonization between Bt and non‐ Bt maize have most often been reported 60 days or less after sowing, indicating that plant developmental stage may be an important contributor to differences in AMF colonization between Bt and non‐ Bt cultivars (Seres et al . ). Nutrient limitation and AMF spore density in soil have also been identified as important factors contributing to differential levels of AMF colonization observed in the roots of Bt and non‐ Bt maize (Cheeke et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, Cry1 toxin groups have lethal effects on caterpillars, while Cry3 toxin groups have the same effects on some beetle larvae. Soil-borne bacteria usually have unique strategies for surviving in the soil, including sporulation and the production of toxic secondary metabolites (allelochemicals) that may modify the colonization of neighboring microorganisms [ 42 ]. Crop residues are the source of carbon in soil, and changes in their nutritional quality may also modify the activity of these organisms [ 9 , 43 ].…”
Section: Discussionmentioning
confidence: 99%